2017
DOI: 10.18632/oncotarget.15600
|View full text |Cite
|
Sign up to set email alerts
|

LMP1+SLAMF1high cells are associated with drug resistance in Epstein-Barr virus-positive Farage cells

Abstract: How Epstein-Barr virus (EBV) affects the clinical outcome of EBV-positive diffuse large B-cell lymphoma (DLBCL) remains largely unknown. The viral oncogene LMP1 is at the crux of tumorigenesis and cell survival. Therefore, we examined the association between LMP1high cells drug resistance. We first assessed SLAMF1 as a surrogate marker for LMP1high cells. LMP1 and its target gene CCL22 were highly expressed in SLAMF1high Farage cells. These cells survived longer following treatment with a combination of cyclop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…A copy number gain at 1q23.3 resulting in strong CD150 overexpression is observed in 30.8% of EBV positive DLBCLs case [74]. Moreover, cells with high level of CD150 and LMP1 expression from EBV positive DLBCL derived cell line Farage are characterized by increased resistance to CHOP therapy compared to CD150 low cells [75].…”
Section: Regulation Of Cd150 Expressionmentioning
confidence: 99%
“…A copy number gain at 1q23.3 resulting in strong CD150 overexpression is observed in 30.8% of EBV positive DLBCLs case [74]. Moreover, cells with high level of CD150 and LMP1 expression from EBV positive DLBCL derived cell line Farage are characterized by increased resistance to CHOP therapy compared to CD150 low cells [75].…”
Section: Regulation Of Cd150 Expressionmentioning
confidence: 99%
“…Given the evidence that LMP-1, an oncoprotein encoded by EBV, mimics the constitutively activated CD40 signal in B lymphocyte responses 42 , it is plausible that IL-21 induces EBV-positive DLBCL cell proliferation by a similar mechanism. It has also been reported that cells with high LMP-1 expression are responsible for the poor drug www.nature.com/scientificreports/ response of EBV-positive DLBCL 43 . Combining these results with our previous observations, we hypothesise that the LMP-1 induced in EBV-positive DLBCL cells may be a key factor for proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there was no significant difference in cell cycle distribution among the cell lines ( Fig 2B). We observed overexpression of SLAMF1 at the cell surface of drug resistant Farage cells [14]. We therefore tested whether SLAMF1-deficient Farage cells responded differentially to drugs targeting several pathways.…”
Section: Differential Response To An Akt Inhibitormentioning
confidence: 99%
“…SLAMF1 was known to costimulate proliferation of activated B cells [3]. In a previous study [14], we used SLAMF1 as a surrogate marker for LMP1 and observed that the SLAMF1 high cells grew faster than the SLAMF1 low cells. However, loss of SLAMF1 itself did not obviously alter cell proliferation and cell cycle distribution at the exponential growth phase.…”
Section: Plos Onementioning
confidence: 99%